Perkembangan Kompetensi Pedagogik Guru Kelas Di Sekolah Dasar: Analisis Survei - Mardicko, Afri; Fatahillah, Fatahillah; Pangestu, Amanda Kurnia (Mafa Press in Collaboration with PGMI Tarbiyah Faculty IPMAFA, 2025)
This research aims to analyze the level of pedagogical competence of class teachers in elementary schools (SD) in Pagelaran District, Pringsewu Regency, Lampung. Teacher pedagogical competence is a key factor in improving the quality of learning and student learning outcomes. However, based on initial observations, it was found that the average teacher's pedagogical competence was still relatively low. Gaps in the mastery of pedagogical competencies, especially in rural areas, have not been studied much through empirical data-based survey approaches. The research method used is descriptive quantitative with a survey approach. The sample consisted of 50 class teachers selected using cluster sampling techniques from 15 state elementary schools. Data was collected through a Guttman scale questionnaire and analyzed descriptively, with validity and reliability tests to ensure the quality of the instrument. The research results show that the majority of teachers have high pedagogical competence, especially in understanding student characteristics (95%), mastering learning theory (94%), and being able to develop a curriculum (92%). Overall, 96% of teachers fell into the